Allocation of Australia's research dollars: does injury research funding reflect injury burden?. (1st March 2011) - Mitchell, R; McClure, R; Olivier, J; Watson, W
Abstract : Introduction: Burden of disease estimates have been used to inform prioritisation of research needs. In Australia, National Health Priority Areas (NHPAs), of which injury prevention is one, have been identified as priorities for prevention and research. The National Health and Medical Research Council (NHMRC) is the principal source of medical research funding in Australia. This research aims to examine NHMRC funding for each NHPA to quantify the relationship between grants awarded and burden of disease measures. Method: A retrospective analysis of NHMRC funding from 2000 to 2008 to assess the strength of correlation between level of funding and the contribution of each NHPA to burden of disease measures (YLD, YLL, DALY) and health system expenditure was conducted. Also examined were observed versus expected research grants by grant type relative to the proportional contribution of each NHPA to DALYs. Results: There were 6099 new and continuing grants awarded, ranging from a total of A94.6 to A423.3 million during 2000–2008. Both YLL and DALYs were strongly correlated with NHMRC funding. Injury received a lesser number of scholarships, overseas training fellowships, career awards, research project and programme grants than what would be expected based on its proportional contribution to total NHPA DALYs. Conclusion: Injury research and investigator training appears to be underfunded by the NHMRC in Australia based on burden of disease measures. Investigator training dollars should be allocated to ensure an optimum workforce distribution that is capable of undertaking research in areas deemed to be of national importance.